Beyond integrity systems: The role of board governance in shaping corporate tax avoidance in global oil and gas companies - I Nyoman Putra Yasa; Gede Teguh Prasetya Muttiwijaya; Rikky Rundu Padang; I Dewa Gede Anom Jambe Adnyana (Universitas Islam Malang, 2026)
Corruption and tax avoidance remain persistent governance challenges in the global oil and gas industry. Although prior studies have examined corruption, board governance, and tax avoidance separately, limited evidence explains how firm-level anti-corruption practices and board governance jointly shape corporate tax behavior in this high-risk industry. This study examines the effect of anti-corruption practices on tax avoidance and the moderating role of board characteristics using data from 100 large-cap publicly listed oil and gas companies over the 2021–2024 period. Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS is employed, while tax avoidance is measured using the Cash Effective Tax Rate (CETR). The results show that stronger anti-corruption practices significantly reduce tax avoidance. Board characteristics also significantly strengthen this relationship and exhibit a stronger association with tax avoidance than anti-corruption practices alone, suggesting that effective boards translate integrity systems into strategic tax decisions. These findings provide an integrated governance perspective by demonstrating that corporate tax behavior depends not only on anti-corruption practices but also on board governance capacity in complex multinational industries.